Therapeutic Effect of Intense Pulsed Light (IPL) Combined with Meibomian Gland Expression (MGX) on Meibomian Gland Dysfunction (MGD) - Shanshan Wei; Xiaotong Ren; Yuexin Wang; Yilin Chou; Xuemin Li (Journal of Ophthalmology)
Purpose. Our study aimed to evaluate the efficiency of intense pulsed light (IPL) combined with meibomian gland expression (MGX) in treating meibomian gland dysfunction (MGD). Methods. This study was a prospective interventional study. A total of 53 patients were included in the study and received a series of three treatments at an interval of 3-4 weeks. Follow-up examinations were completed 4 weeks after the last treatment. The Ocular Surface Disease Index (OSDI) questionnaire, tear meniscus height (TMH), tear break-up time (TBUT), slit-lamp examinations, and in vivo confocal microscopy (IVCM) were recorded before and after treatment. Additionally, an artificial intelligence automated software program was applied in our study for corneal nerve analysis. Results. The OSDI score was significantly reduced after the IPL treatment compared with baseline (P<0.001). Meibomian gland assessment scores, including meibum quality and expressibility, eyelid margin abnormalities, and corneal staining, significantly decreased after treatment (P<0.05). Moreover, the corneal nerve fiber length (CNFL) significantly increased after the treatment (P<0.001). Conclusion. Intense pulsed light (IPL) combined with MGX is an effective treatment for MGD, and neurotrophism could be one of the mechanisms of IPL.